1989
DOI: 10.2165/00003088-198917020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics in Patients with Spinal Cord Injuries

Abstract: Although spinal cord injury is a catastrophic affliction with numerous victims and a variety of physiological manifestations, the associated disarray in physiology has yet to be systematically or comprehensively studied as a probable cause for altered pharmacokinetics. A significant increase in the volume of distribution of drugs such as the aminoglycosides (gentamicin, amikacin, tobramycin), which are highly distributed into the extracellular fluid space and minimally biotransformed, may be anticipated in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…Studies on intramuscular administration of cefotiam and gentamicin have confirmed that both present delayed absorption and lower peak serum concentrations. 40 Absorption of diclofenac through intramuscular administration, however, was unaltered in SCI patients. 41 Further studies are needed to understand the distinct behavior of drugs and the physiological anomalies that cause PK alteration after intramuscular administration.…”
Section: Altered Pkmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on intramuscular administration of cefotiam and gentamicin have confirmed that both present delayed absorption and lower peak serum concentrations. 40 Absorption of diclofenac through intramuscular administration, however, was unaltered in SCI patients. 41 Further studies are needed to understand the distinct behavior of drugs and the physiological anomalies that cause PK alteration after intramuscular administration.…”
Section: Altered Pkmentioning
confidence: 99%
“…Studies have shown that increases in the volume of distribution post-SCI can range from 20% for amikacin to 70% in cases such as cefotiam. 40 Other drugs with altered distribution due to an increase in volume of distribution include ketamine and lorazepam. 46,47 Moreover, altered serum lipid profile affects the quantity of drug that can bind and be distributed.…”
Section: Altered Pkmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Likewise, SCI-induced changes in oral drug absorption have been reported for paracetamol, 4,7 dantrolene 8 and theophylline, 9 and it has been suggested that these changes could have an impact on the efficacy and safety of a variety of drugs in this population. 10 Characterization of the pathophysiological alterations underlying pharmacokinetic changes that occur in patients with SCI has been complicated because of the important variability induced by differences in injury characteristics, as well as in the individual conditions of each patient. 10 Moreover, not all drugs exhibit altered disposition after SCI.…”
Section: Introductionmentioning
confidence: 99%